Pengaruh Marinasi Larutan Jeruk Lemon (Citrus limon L) Terhadap Karakteristik Organoleptik Sate Ayam - Yunita, Citra Nurma; Devi Kusuma Pradana; Reza Fahlevi; Sari Dewi; Reo Radius Falah (Universitas Muhammadiyah Kotabumi, 2025)
Lemon is one of the natural ingredients that has the potential to be applied as a marinade in processed meat products such as satay. This study aims to determine the optimal percentage of lemon solution producing the best sensory quality in chicken satay products. The materials used in the study were chicken meat and local lemons. The study was conducted experimentally with different percentage treatments of lime solution, then organoleptic tests were carried out by trained panelists. The treatments consisted of T0: without lemon solution marinade, T1: 6% lemon solution marinade, T2: 9% lemon solution marinade, and T3: 12% lemon solution marinade. The data from the Completely Randomized Design (CRD) were then analyzed using ANOVA and continued with the Duncan test if there was a difference. The results showed that lemon solution marinade had a significant effect (P <0.05) on the organoleptic color, aroma, taste, and texture. The average color value is 3.72-4.80, aroma 3.32-4.72, taste 3.60-4.84, and texture 3.32-4.80. This study can be concluded that the T3 treatment (12% lemon marinade) is the most optimal, with an average color score of 4.40, aroma 4.72, taste 4.84, and texture 4.80, because it can produce the best sensory quality by improving the taste, aroma, and texture of chicken satay. The results of the study are expected to be a reference for the culinary industry in improving the quality and competitiveness of processed meat products made from chicken